Digital Wisdom : A Reconstruction of Christian Leadership Theology in the Age of Algorithms and Echo Chambers - Andre Shevcenco Mumu (International Forum of Researchers and Lecturers, 2025)
The era of technological disruption, driven by the economic logic of